Experimental and simulation investigation into the effects of a flat plate deflector on vertical axis wind turbine - Wong, Kok Hoe; Chong, Wen Tong; Sukiman, Nazatul Liana; Shiah, Yui Chuin; Poh, Sin Chew; Sopian, Kamaruzzaman; Wang, Wei Cheng (Elsevier, 2018)
Power augmentation features have been proven as one of the wind turbine performance enhancement methods particularly for vertical axis wind turbines (VAWTs). Researches showed that with the aid of a deflector, shroud or a single plate, the power output of a VAWT can be increased remarkably. In this paper, lab tests and simulations were performed to investigate the aerodynamic effects and the flow field around a flat plate deflector as a power augmentation device which is placed at the lower upstream of a micro H-rotor VAWT. From the study, the deflector is able to induce a high velocity wind at the near-wake region which was about 25% higher compared to the oncoming wind velocity. The deflected wind flows improve the performance significantly as well as reduce the self-start velocity of the turbine. Nonetheless, it is highly dependent on the positioning of the flat plate deflector. Both experiment and simulation showed a notable observation on the position effect of the flat plate deflector. From the lab test, with the deflector at the optimal position, the maximum coefficient of power (CP) achieved was 7.4% increment compared to the bare turbine. Also, from the simulation, the optimal position showed an improvement of averaged CP up to 33% compared to the bare turbine. The flat plate deflector is simple, low cost, and can be easily retrofitted to existing stand-alone VAWT systems to improve the efficiency making them suitable for on-site power generation in urban and isolated places.